Genotype by environment interaction and stability analyses of advance blast resistant rice genotypes derived from crossing between MR219 and Pongsu Seribu 2 - Sabri, Raieah Saiyedah (2019)
Multi-environmental yield trials is vital in assessing the newly developed rice genotypes for its adaptability and stability across environments especially when the objective to release the newly developed variety for commercial cultivation. The growth performance and phenotypic variability of these genotypes are the combination of environment, genotype and genotype by environment (G×E) interaction factors, thus evaluation must be done since it creates an opportunity for an effective selection of superior genotype. In this study, 18 improved blast resistant rice genotypes developed from the crossing between MR219 and Pongsu Seribu 2 including MR219 as recipient parent were evaluated under four different environments in Peninsular Malaysia. The experiments were carried out using randomized complete block design with three replications at each environment. Data were collected on the vegetative, yield and yield component traits. Analysis of variance revealed significant differences among the genotypes, environments and G×E interaction for most of the traits under study. Low heritability (<30%) was found for all the traits. Similarly, low genetic advance was also observed for all the traits except for number of tillers per hill and number of panicles per hill. Correlation coefficients observed with yield per hectare showed a significant and positively correlated with most evaluated traits except for days to flowering, days to maturity, plant height and number of unfilled grains. Cluster analysis divided the 19 evaluated genotypes into six groups. The recipient parent, MR219 was clustered with G17 and G18. Stability analyses classified the rice genotypes into three groups based on the univariate (bi, S 2 d, σi 2 , Wi 2 , YSi) and multivariate stability statistics. The first group consisted of genotypes such as G11, G17, G118 and MR219 that were having high mean yield trait with high stability. These genotypes were widely adapted across environments. The genotypes in the second group such as G1, G6 and G8 had possessed characteristic with high mean yield trait but low stability, which are suitable for cultivation at a specific environment. The last group included genotypes having low mean yield trait but high stability for example genotypes G7, G9 and G13. Tanjung Karang 1 environment was the most suitable environment for majority of the genotypes revealed by environmental discriminate analysis using GGE biplot. This followed by Serdang and Kota Sarang Semut, meanwhile Tanjung Karang 2 was the poorest environment for the genotypes selection. From this study, superior genotypes namely G18, G17, G11, G14, and G5 had produced high yield and highly stability across diverse environments are recommended for large scale evaluation before commercial release to rice farmers.